Pemberdayaan Organisasi Masyarakat melalui Pembentukan Event Organizer Bazar Kuliner (Studi pada Organisasi Masyarakat Desa Ciawi, Brebes) - Muhamad Syahrul Aziz; Hendri Sucipto; Slamet Bambang Riono (BADAN PENERBIT STIEPARI PRESS, 2022)
Ciawi Village is a village located in Banjarharjo District, Brebes Regency. In Ciawi Village, there are several community organizations such as Ms. PKK, Karang Taruna, Branch NU, and IPPNU. During the observation, several community organizations were found in Ciawi village. However, during interviews with the village government, the activity of community organizations was still weak. The reason is because there is a problem that occurs both from internal and external communication. This is what makes the author take the theme of organizational empowerment through the formation of an event organizer (EO) and the implementation of a culinary bazaar. EO itself is currently needed by many parties, not only companies or organizations in urban areas but also organizations in villages as an effort to introduce their villages and take advantage of existing opportunities. Ciawi Village itself, although the smallest village, has a position flanked by 4 villages at once, namely to the north of Cimunding Village, south of Tegalreja Village, west of Cibuniwangi Village and east of Keradenan Village. Based on the results of the activities that have been carried out, several community organizations have begun to understand the course of the culinary bazaar EO to be used as a way to improve the village economy through MSME activities, it can be concluded that the structural formation of a culinary bazaar event organizer has a great impact on the community both for MSME actors organizations, village government and village communities.